Effects of ageing on the initial metabolic response to accidental injury - Barton, R; Frayn, K; Stoner, H; Little, R (1998)
Background: little is known about the effects of ageing on the early metabolic response to injury. This response is thought to have evolved as a defence mechanism and may be particularly important in old people, who often present late to hospital after accidental injury. Setting: the accident and emergency department of a teaching hospital. Subjects: 352 patients studied within 2 h of accidental injury, before the start of definitive treatment. Methods: a single blood sample was taken from each patient and the plasma concentrations of glucose, insulin, lactate, non-esterified fatty acids and cortisol were measured. Factorial analysis of variance was used to distinguish the effects of age (17-40, 41-65 and 66-92 years) from those of Injury Severity Score (1-6, 8-12, 13-24 and 25-66). Results: elderly patients had a higher concentration of glucose than young ones. There were no consistent age-effects for the other analytes. Although men were over-represented among the young and women among the elderly, a similar analysis by sex in the 41-65-year-old group suggested that this uneven distribution did not bias the results. Conclusion: elderly people do not have a defective early biochemical response to injury.